3(x+2)=(3x-4)

Simple and best practice solution for 3(x+2)=(3x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+2)=(3x-4) equation:



3(x+2)=(3x-4)
We move all terms to the left:
3(x+2)-((3x-4))=0
We multiply parentheses
3x-((3x-4))+6=0
We calculate terms in parentheses: -((3x-4)), so:
(3x-4)
We get rid of parentheses
3x-4
Back to the equation:
-(3x-4)
We get rid of parentheses
3x-3x+4+6=0
We add all the numbers together, and all the variables
10!=0
There is no solution for this equation

See similar equations:

| 7.7-0.5x=4.7 | | 3^(4-x)-7=74 | | 5(4x-1.5x)+12=12=4x-2 | | 25-30x=65+20x | | 16y-6=14 | | 5.45+x=8 | | (3m+1)(-2)=11 | | 3(6x-3)=99 | | 0.7=y/4 | | 2/3=1/3(x-4) | | 4.7=7.7=0.5x | | 2x-5=10x+20 | | 3/5=3/5x+4 | | 6m(m-6)=0 | | 4g+3.72=20.84 | | -2(3a-2)=88 | | 54+m=73 | | D=166t^2 | | -2v–3v=45 | | 2(3+4m)-9=5 | | 0.09+0.13(k+300)=61 | | -34+n=15 | | 5/12(x)=-0.75 | | 9w-14=-4 | | 20.84=4g+3.72 | | 16x+1=28x+3 | | 28x+3=16x+1 | | 4t+5=8t+4 | | 4x-6x=25 | | 5/3*3/2=y | | 5/12x=-0.75 | | 1x•2=4 |

Equations solver categories